Bilateral spontaneous pneumothorax in a term newborn - James, Vinson; Rajan, Jincy (Indian Journal of Case Reports, 2020)
Spontaneous pneumothorax in a full-term, apparently healthy infant is rarely seen, although it is a well-known complication of the respiratory distress syndrome. The management is mostly associated with assisted ventilation, birth trauma, meconium aspiration, or prematurity. We report the case of the occurrence of spontaneous bilateral pneumothorax in a healthy neonate, born by spontaneous vaginal delivery at term in the absence of any known predisposing factors. The baby recovered completely with conservative management with an oxygen-enriched atmosphere and needle thoracentesis. Symptomatic spontaneous pneumothorax is a rare occurrence in term newborns. Bilateral spontaneous pneumothorax has only been described only in a handful of case reports until now. Early recognition of progressive respiratory distress and its immediate management is lifesaving and reduces undue interventions, referrals, escalation of treatment costs, and the hospital stay.